Social cognitive theory and women’s career choices: an agent—based model simulation - Najib A. Mozahem (14150970) (2022)
An agent-based model is proposed and tested. This model aims to simulate agency as conceptualized in Bandura's (Am Psychol 37:122–147, 1982; Organ Behav Hum Decis Process 50:248–287; Annu Rev Psychol 52: 1–26) Social cognitive theory. Social cognitive theory has been used to explain the continued underrepresentation of females in certain fields, most notably fields that are associated with engineering and technology. The theory proposes that agents acquire information from four different sources, and then, through a process of reciprocal interaction, these agents develop their perception of self-efficacy. In this study, an agent-based model is used to model this interaction. The output from the simulation supports the validity of the model used and illustrates how agency "emerges" from the triadic interaction. The model successfully simulates several of the theorized aspects of social cognitive theory. The simulation results reveal that even small gendered differences can lead to female misrepresentation in certain fields. The model also shows that female discouragement plays a larger role than male encouragement in female underrepresentation. The implications of these results are discussed. Finally, the limitations of the model are discussed, along with directions for future research. Other Information Published in: Computational and Mathematical Organization Theory License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10588-020-09317-6